Arabic Phonological Interventions with Mimicry-Memorization Learning Method: A Review on Evidence-Based Treatment - Tulus Musthofa; Rihanatul Fauziah (Graduate School of Universitas Negeri Malang, 2021)
Abstract: Difficulties and errors in the pronunciation of Arabic phonology still often occur in the process of learning Arabic by non-Arab students it is due to lack of attention in teaching Arabic phonology by teachers and non-Arab students. But in previous studies, no one has researched the use of methods in the learning. Thus in this study, researchers have explored, analyzed, and described a method to give an overview of a method for learning Arabic phonology for foreign students. This research uses the Library research method in the collection of relevant data. Data is obtained from articles, books, Internet and past research by the discussion. The result is that the mimicry-memorization method has a lot to influence the results of foreign language learning and can be used as an innovation in Arabic phonology learning for foreign students, which is the most key thing to do before learning Arabic language skills. Thus the results of This research can provide innovations for teachers of Arabic with a method of mimicry-memorization in teaching Arabic phonology to foreign students so that they can pronounce the letters, vocabulary and sentences of Arabic language well and correctly. Thus, non-Arab students can communicate with Arabic in communicative, eloquent, and fluent.